The cultural identity of São Borja in the region of the Seven Peoples of the Missions in Rio Grande do Sul - Araújo, Claudio Gabriel Soares; Rückert, Aldomar Arnaldo (Seven Editora, 2023)
This article aims to identify the representation of cultural identity in the public space of the city of São Borja whose historical evolution and development justify the existence of artifacts that represent the cultural diversity of the place. The research pointed to the potential that the city has to contribute to the appreciation of local, regional and territorial cultural historical heritage through historical and cultural tourism. The research identified the need for alignment of public policies for the economic, social and cultural development of the city of São Borja with the other cities of the Region of the Seven Peoples of the Missions, as well as pointed to the development of tourism as an alternative for territorial development. The study was developed in three stages, the first being through a bibliographic and documentary research followed by a field research that used the participant observation method to collect primary data. The third stage was data analysis, selection of information and theoretical construction in the form of an article containing the research and the results obtained. DOI:https://doi.org/10.56238/ptoketheeducati-007